Crystal structures of high temperature quantum paraelectrics Na 1/2Nd1/2TiO3 and Na1/2Pr 1/2TiO3 - Ranjan R.; Agrawal A.; Senyshyn A.; Boysen H. (My University, 2025)
Both neutron and x-ray powder diffraction studies have been carried out for two high temperature quantum paraelectrics, Na1/2Nd 1/2TiO3 and Na1/2Pr1/2TiO 3. Although visual inspection of the diffraction patterns suggests a 'nearly cubic' like structure, careful analysis of powder neutron diffraction patterns and comparison of Rietveld refinement results for competing models reveal that both compounds belong to the orthorhombically distorted GdFeO 3 type of structure (Pbnm space group, a-a -c+ tilt system in Glazer notation). The full set of refined structural parameters is reported for the first time. The relationship between octahedral tilt angles and dielectric softness of these compounds is briefly discussed. © 2006 IOP Publishing Ltd.